Model Propagasi Komunikasi Bergerak LTE 1800 Mhz Di Kota Pekanbaru - Sutoyo Sutoyo; Indika Herni; Muhammad Luthfi Hamzah; Mulyono Mulyono (INTECOMS: Journal of Information Technology and Computer Science, 2020)
Propagation model is an important part that can be used to design a communication network one of them is mobile communication. The difference in the propagation signal received from the transmitter to the mobile station will result in loss propagation so we need a propagation model that can describe the propagation characteristics of a region such as urban areas in this case is Pekanbaru City. To get the propagation model in accordance with the characteristics of Pekanbaru City the method used is measurement through a drive test. This research aimsto determine the mobile communication propagation model in LTE 1800 MHz that fits the characteristics of Pekanbaru City. Based on the results of the measurement of the value of loss to distance obtained by the propagation model of mobile communication in the city of Pekanbaru with 3 models of the equation, among others linear equation model: L = 5.1 x D + 85, quadratic equation: L = 2.2 x + 3 x + 86 and cubic equation: L = 0.65 x + 0.84 x + 3.6 x D + 86.